Measuring the impact of the economic balance goals on the economic growth of the Iraqi economy for the period (1990-2023) - Faraj, Sikna Jahya (Journal of Economic, Administrative and Legal Sciences, 2025)
Achieving economic balance is a multifaceted and ongoing goal. Its achievement requires effective policy making and strategic investments capable of adapting to changing economic conditions. It is a dynamic goal that governments and policy makers around the world seek to achieve for the benefit of their countries by implementing a set of strategies and plans that will Achieving a more balanced and resilient economy, ultimately leading to greater prosperity and improved quality of life for the community. The research aims to determine the impact of the objectives of economic balance (national income, unemployment rate, inflation rate) on economic growth in the Iraqi economy for the period (1990-2023), and to determine the impact of inflation, unemployment, and national income as objectives of economic balance and how they affect economic growth. The researcher relied on the descriptive analytical method, The study also recommended the need for coordination and harmonization between monetary and financial policy so that there is no contradiction between the goals and the possibility of achieving stability, reducing inflation and unemployment rates, and achieving economic growth through testing the limits of co-integration within the autoregressive methodology of distributed time lag based on the existence of a long-term equilibrium relationship between the rate of economic growth and national income. And the rate of unemployment and inflation, although the decline in economic growth was mainly caused by wrong policies and the state’s control over the overall economic activity and the accompanying mismanagement and the inability to diagnose the effective factors in achieving development and the loss of the standards necessary to make appropriate economic decisions, which was reflected in the overall economic activity and was accompanied by that. High unemployment rates in the Iraqi economy.